HUBUNGAN STATUS GIZI, KEBIASAAN MAKAN DAN AKTIVITAS FISIK DENGAN PERSEPSI BODY IMAGE PADA REMAJA PUTRI DI SMA NEGERI 2 KOTA BEKASI - Natalia Cristine Siagian (2022)
Adolescence is a period when a person is aged 10-19 years, who experiences psychological, biological and sociological development that are related to one another. Body image is a view of individuals, both male and female, on the appearance of their body shape and each has an assessment of its shape, which is influenced by behavior, other people's perceptions, emotions, physical experiences, friends, and the surrounding environment. This study aims to analyze the relationship between nutritional status, main meal frequency, snack eating habits and physical activity with the perception of body image in adolescent girls at SMAN 2 Bekasi City. This research is analytic observational with a "case control" which has a sample size of 68 respondents using stratified random sampling and simple random sampling and was carried out in May - June 2022. The results of the bivariate test with chi-square indicate a relationship between status nutrition (p=0.021; OR=5.76), main meal frequency (p=0.015; OR=0.292), snack eating habits (p=0.015; OR=3.378), and physical activity (p=0.21; OR = 0.292) with the perception of body image in young women. It is expected to read education about knowledge of balanced nutrition in order to understand about eating habits and knowledge of good nutrition so as not to cause negative body image perceptions.